Exploring the diverse factors in accessing formal financing of MSMEs the case of retail sector in Tacloban City - Angulo, Missy Angel P.; Gabas, Mae Flor C.; Garras, Jhoanne A.; Yu, Jay Mark C.
Developing economies rely heavily on the contribution of Micro, Small, and Medium Enterprises (MSMEs) in promoting economic growth and employment creation. In the Philippines, MSMEs were known to be a means out of poverty, especially for residents living in remote and rural areas. However, despite their significance, MSMES face challenges when accessing external sources of finance, while other businesses benefit from factors enhancing financial inclusion. This research aims to bridge the gap in knowledge by exploring the difficulties or ease factors that MSMEs in the retail sector of Tacloban City encounter when accessing formal sources of finance. This research utilized a qualitative research design, particularly an exploratory case study, and a purposive sampling technique to select fourteen interviews among MSME owners in Tacloban City. Additionally, Thematic Analysis was utilized in the data gathering analysis to identify, analyze, and interpret the recurring themes. The findings showed six factors that help MSME owners apply for formal financing, namely office proximity, good relationships. membership, institution initiatives, complete requirements, and government initiatives. Overall, the result defies the belief that MSME owners encountered difficulties accessing formal finance. The data reveals that they found no challenges in getting access to formal finance because the participants were fulfilling requirements and building good. relationships with financial institutions while leveraging on memberships and programs, taking advantage of readily available office facilities within the institution, and seizing initiatives. Furthermore, we recommend to all future researchers, to further research employing diverse methodologies to gain a deeper understanding of the observed. deviation.